Media Learning Social Studies For Teacher Member MGMP Social Studies Sintang Regency - Ambros Leonanggung Edu; Bernieke Damanik; Dini Anggraeni Dewi; Ahmad Amin; Tonia Sharlach (Marsiurupan: Journal of Community Development and Empowerment, 2026)
The purpose of community service is: 1) Teachers can choose the right learning media. using existing sources; 2) Efforts made to design the right learning media to support the learning process between students and teachers in schools; 3) Increase teachers' insight into the nature of innovative learning media and development procedures, so teachers are motivated to develop instructional media appropriate to the characteristics of their students. Alternative problem solving is through seminars or counseling. Stages of activities include Preparatory Phase, Implementation Phase and Activity Evaluation. This community service is held on September 20, 2017, located at State Junior High School 1 Tempunak, Sintang District. the participants of the activities are the Integrated IPS teachers who are members of the MGMP IPS of Sintang District. Implementation of devotion in two sessions: in the first session of material delivery by both presenters. In the session in the form of media demonstration of teaching and learning questions of participants and participants. Based on the results of activities undertaken to improve teachers' knowledge about integrated IPS learning media